Internal Quality Assurance System On Learning Management Standards In Midwifery D3 Study Program Lampung Province - et. al., Nurhidayah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In accordance with the mandate of the National Education System Law (Law No. 20 of 2003 Article 50) that the management of national education is based on national policies and national standards to ensure the quality of national education. The policy is strengthened again in article 51 paragraph (2) explaining that the management of higher education units is carried out based on the principles of autonomy, accountability, quality assurance, and transparent evaluation. Furthermore, in Law No. 12 of 2012 Article 52 stated that the quality assurance of higher education is a systemic activity to improve the quality of higher education in a planned and sustainable manner, as well as quality assurance as intended through the principle of determination, implementation, evaluation, control, and improvement (PPEPP) of Higher Education standards. Prodi D3 midwifery lampung province has declared itself through the vision as a study program that is able to produce qualified midwifery experts based on local wisdom with a global insight. The commitment is set forth in academic quality policy with the principle of quality culture management. Consequently, the History program established an internal quality assurance unit called the Quality Assurance Unit (UPM). UPM as the controlling unit of the Implementation of Internal Quality Assurance System (SPMI) plans, implements, and develops academic and nonacademic quality assurance system by compiling a script in the form of SPMI Policy, SPMI Manual, SPMI Standard, SPMI form document, and Oprational Prosedure Standard (SOP). The quality policy of Prodi D3 midwifery in Lampung Province contains quality commitment to prioritize services to produce graduates who satisfy stakeholders. Therefore, quality standards must be formulated in accordance with the National Standard of Higher Education (SNDikti). Silkus spmi implementation in Prodi D3 midwifery adjusted to 5 (five) main steps namely PPEPP. UPM Prodi D3 midwifery lampung province as a quality controller must always conduct SPMI in accordance with 5 (five) main steps in a planned and sustainable as an effort to improve academic quality continuously (continuous quality improvement) especially the standard of learning management Good actions that must be done to ensure the improvement of academic quality, especially the management of defense in a sustainable manner by following 5 (five) main steps of implementing SPMI